Stomoxys calcitrans influence the outcome of lumpy skin disease virus inoculation in bovine experimental models - Charlotte Cook (2022)
The poxvirus lumpy skin disease virus (LSDV) is the etiological agent of lumpy skin disease (LSD), a severe, systemic transboundary disease of cattle and water buffalo. LSD is a rapidly emerging disease, spreading into and across the Middle East, eastern Europe, and Asia in the past decade, and which is now threatening bovine inventories in Australia. The disease presents as cutaneous lesions that can become necrotic, as well as pyrexia and reduction in milk and meat yields, causing substantial production and economic losses in rural communities.